Hábitos de lectura y consumo de información de los adolescentes en el ámbito digital - Rosa Tabernero Sala; Eva Álvarez Ramos; Hugo Heredia Ponce (Investigaciones Sobre Lectura)
The present work tries to echo how the communicative metamorphoses occurred in the last years, inferring in the reading habits and in the consumption of information in a general way and more specifically in adolescents. The analysis will start from the report prepared by the writers’ guild 2018 (2019), since it allows us to monitor the state of reading habits and book purchases in a generalized way in Spain. Then, apply what has been poured out to young people extensively and, finally, materializing by extrapolating all the data analyzed to the geographical area of Cádiz adolescents and their position in relation to the rest of Spanish adolescents. Gender variables will also be taken into account in a very special way, to see if there is a certain preference depending on the sex of the reader in the choice of medium (digital or analogue) and if within the digital medium there are discrepancies in the type of text read. We will also check whether digital reading by young people is reduced exclusively to short texts and whether this choice can be derived from the very nature of digital. In the same way, we will pay special attention to the preferences of analogical reading versus digital reading, when we talk about long texts, again due to the personal nature of paper reading. We will analyze the reading frequency of the different digital media, as well as the choice of other shorter texts, categorized within the taxonomy of digital reading. Finally, we will take into account what types of readers with respect to reading frequency become from digital media. The idea is to draw up a panorama that shows how reading occurs among adolescents in the digital world, by definition, closer to their thoughts and feelings.